THE MAIN SOURCE OF THE ORIGIN OF PROVERBS AND SAYINGS AND THEIR ROLES IN LEARNING FOREIGN LANGUAGE - Otajonova Kamola (Scholars Digest Publishing, 2023)
The main point of the article is that there is a cruсial question about how and where proverbs and sayings came from. Then some opinions are given that the main source of the origin of them is folk and it would be more correct to say that the main primary source in the collective mind of the people. Besides, it is said that there is undeniable importance of the proverbs in learning foreign languages. Learning a language from the very beginning should go in conditions of real communication or imitate these conditions as accurately as possible. Therefore, one cannot underestimate the enormous methodological and practical value of using proverbs and sayings in the process of teaching a foreign language in high school.
Keywords: alien proverbs, borrowed proverbs, folk art, diverse phenomena, English proverbs.